1990
DOI: 10.1079/bjn19900005
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intakes, vitamin–mineral supplementation, and intelligence in British schoolchildren

Abstract: ~Children (227), aged 7-12 years, weighed and recorded all food and drink consumed for seven consecutive days. Each child completed tests of verbal and non-verbal intelligence, and was then randomly allocated to one of two groups after matching for age, sex, IQ and height. In a double-blind trial lasting for 28 d, one group received a vitamiwmineral supplement daily and the other group a placebo. On re-testing, there were no significant differences in performance between the two groups. Furthermore, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 11 publications
(11 reference statements)
6
36
1
Order By: Relevance
“…s Total nutrient intake Total nutrient intakes in the DONALD Study are in good accordance with results of representative cross-sectional European studies using dietary records, e. g. in the Netherlands [23], Greece [24], Spain [18], and England [25]. The only longitudinal study in children and adolescents of the same ages as the subjects of the DONALD Study originates from the Netherlands [23] where total intake of some nutrients (calcium, iron, vitamin A and C) was assessed in 1987/88, 1992 and 1997/98.…”
Section: Discussionsupporting
confidence: 59%
“…s Total nutrient intake Total nutrient intakes in the DONALD Study are in good accordance with results of representative cross-sectional European studies using dietary records, e. g. in the Netherlands [23], Greece [24], Spain [18], and England [25]. The only longitudinal study in children and adolescents of the same ages as the subjects of the DONALD Study originates from the Netherlands [23] where total intake of some nutrients (calcium, iron, vitamin A and C) was assessed in 1987/88, 1992 and 1997/98.…”
Section: Discussionsupporting
confidence: 59%
“…The increases in IQ observed in these studies were substantial. Two other studies have demonstrated only a slight increase in IQ in the group given a diet supplementation (Crombie et al, 1990;Nelson et al, 1990).…”
Section: Additional Considerations Concerning Lead and Iqmentioning
confidence: 88%
“…There is only weak evidence of relationships between dietary status and cognitive function, and none which relates directly to Fe, in spite of the fact that ID is the most common nutrient deficiency in the UK (Nelson, 1992). In a study of 143 11-12-year-old schoolchildren from North London, Nelson et al (1990) failed to show significant associations between baseline Fe intakes and cognitive function based on the Heims AH4 test (Heims et al 1976) or two components, digit span and coding, of the Weschler Intelligence Scale for Children, Anglicised Revised Edition (WISC-R UK; Weschler, 1971). There were also no differences observed in the change in cognitive function between a group supplemented with a multi-vitamin and mineral preparation for 28 d and an age-, gender-and height-matched group given a placebo.…”
Section: O G N I T I V E F U N C T I O Nmentioning
confidence: 99%